2003
DOI: 10.1097/01.shk.0000078832.57685.6c
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline Resuscitation Reduces Apoptosis and Tissue Damage of the Small Intestine in a Mouse Model of Hemorrhagic Shock

Abstract: The effect of hypertonic saline resuscitation on intestinal damage and the incidence of apoptosis after hemorrhagic shock were investigated. After anesthesia, male BALB/c mice weighing 24-34 g were hemorrhaged to the mean arterial pressure of 40 +/- 5 mmHg for 90 min. Animals were randomly assigned to four groups: 1) resuscitation with 4 mL/kg of 7.5% NaCl (hypertonic saline; HS) + shed blood (SB); 2) resuscitation with two times the volume of shed blood of lactated Ringer's solution (2LR) + SB; 3) sham (cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 32 publications
1
44
0
4
Order By: Relevance
“…55 A possible interaction between hypertonic saline for the treatment of hemorrhage, apoptosis, and tissue damage of the small intestine has also been recently suggested. 57 In another study, we have shown that hypertonic saline may exert its long-term benefits after hemorrhagic shock by modulating bone marrow apoptosis. 58 , a mechanism that has been linked to sepsis and multiple organ dysfunctions.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
See 1 more Smart Citation
“…55 A possible interaction between hypertonic saline for the treatment of hemorrhage, apoptosis, and tissue damage of the small intestine has also been recently suggested. 57 In another study, we have shown that hypertonic saline may exert its long-term benefits after hemorrhagic shock by modulating bone marrow apoptosis. 58 , a mechanism that has been linked to sepsis and multiple organ dysfunctions.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
“…45 More recently, a series of experiments have shown that hypertonic saline solution, even without dextran, significantly interferes with the immune responses, both in vitro and in vivo. [46][47][48][49][50][51][52][53][54][55][56][57] The addition of hypertonic saline solution to a lymphocyte culture media, in concentrations similar to those obtained with systemic infusion of 4 mL/kg of 7.5% NaCl in humans, determined a significant increase in lymphocyte proliferation. 46 The addition of prostaglandin E 2 (PGE 2 ) to the culture media, in the absence of hypertonic saline, caused a reduction in T-cells proliferation, when compared to control cultures.…”
Section: Immune and Inflammatory Effects Of Hs/ Hsdmentioning
confidence: 99%
“…Resuscitation fluids can also influence inflammatory and immune responses. It has been shown that HES effectively decreases leukocyte adherence, improves endothelial integrity, decreases apoptosis and attenuates tissue edema and injury in different animal and human models of fluid resuscitation (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Os seus benefícios foram demonstrados em várias espécies, como eqüinos (Schmall et al, 1990a(Schmall et al, e 1990b, caninos (Prough et al, 1991;Schertel et al, 1996), bovinos (Constable, 1999), murinos (Murao, 2003), suínos (Hellyer e Meyer, 1994) e ovinos (Taylor, 1999).…”
Section: Introductionunclassified